Xylem morphology determines the drought response of two Arundo donax ecotypes from contrasting habitats. Issue 1 (2nd May 2016) - Haworth, Matthew; Centritto, Mauro; Giovannelli, Alessio; Marino, Giovanni; Proietti, Noemi; Capitani, Donatella; De Carlo, Anna; Loreto, Francesco
Abstract: Arundo donax exhibits rapid growth and requires little nutrient input, making it an ideal perennial biomass crop species. However, this growth is accompanied by high rates of water use, potentially restricting the use of A. donax in rain‐fed marginal lands. Here, we investigated the physiological and morphological responses to drought in two ecotypes of A. donax from contrasting habitats: one from an arid environment in Morocco, and the second from a warm humid sub‐Mediterranean climate in central Italy. Prolonged drought resulted in identical reductions in leaf‐level photosynthesis ( P N ) and stomatal conductance ( G s ) in the two ecotypes. However, water deficit induced an increase in xylem vessel diameter in the Moroccan plants, improving the movement of water along the stem, but also likely reducing the resistance to embolism. In contrast, the Italian ecotype reduced xylem vessel area, thus increasing resistance to water transport and xylem embolism. The increased xylem vessel size and associated vulnerability to embolism in the Moroccan plants may have contributed to an increase in the loss of leaf numbers, but also to higher relative water content (RWC) in the remaining leaves in comparison to the Italian ecotype, where a greater number of leaves persisted. Despite the Moroccan plants possessing stems with a lower basal area than their Italian counterparts, both ecotypes exhibited identical leaf to supporting stem area ratios under both control and water deficit conditions. This may account for the similarities observed in leaf area measures of P N and G s in this and previous studies of different A. donax ecotypes. Selection of A. donax ecotypes on the basis of xylem responses to drought may facilitate the development of varieties suited to arid environments prone to severe drought and wetter habitats where prolonged droughts occur less frequently.